Investment opportunities in Subang Jaya focus on : the popular types of development and their respective yields / Rohainee Muhamad - Muhamad, Rohainee (1994)
This paper is part of the course requirements for the final year students of Advanced Diploma in Business Studies (Finance). This project paper is a study on Subang Jaya township, which consists of Subang Jaya (SS area) and UEP Subang Jaya (USJ area). All the informations are obtained from primary and secondary data. The purpose of study is to determine the average rate of return on residential and commercial properties in Subang Jaya and to find out the most saleable type of houses as well as the factors that influence a buyer to buy properties in Subang Jaya. This study is also conducted to find out whether or not end-financing facilities arranged by the developer help to sell the completed units. The result of the study shows that the average rate of return on investment of other types of properties is above 8% except for rental property, where the rate of return is lower at 6.225%. It is also found that the double storey link house is the most popular and saleable type of house . in Subang Jaya, which comprise of 78.36%. The remaining types include one and a half storey ? apartment7 flat, semi-detached> and bungalows. Strategic location> affordable pricing policy and the solid estate lands are the main reasons why investors prefer to buy properties in Subang Jaya. Eeside their qualities, the developer's credential is also the determining factor which include the quality of the building and as well as the on time completion of each project launched by the developer.